2021
DOI: 10.1007/s40710-021-00530-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Modelling of Micro-pollutants in a Strongly Regulated Cross-border Lowland Catchment

Abstract: Anthropogenically influenced transboundary catchment areas require an appropriately adapted exposure modelling. In such catchments, water management decisions strongly influence and override natural river hydrology. We adapted the existing exposure assessment model GREAT-ER to better represent artificially overprinted hydrological conditions in the simulations. Changes in flow directions and emission routes depending on boundary conditions can be taken into account by the adopted approach. The approach was app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Instead, two different scenarios describing season-specific typical hydrologic conditions were created for the Vecht catchment. A detailed description of the setup and the hydrological representation is provided by Lämmchen et al Its general applicability was recently confirmed by a case study with pharmaceuticals. , The first scenario represents the situation of dry weather in summer (dry summer scenario), and the second one describes humid periods throughout the whole year (average flow scenario), where the flow rate is affected by interflow and surface runoff due to precipitation (see Table S9 for more details).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, two different scenarios describing season-specific typical hydrologic conditions were created for the Vecht catchment. A detailed description of the setup and the hydrological representation is provided by Lämmchen et al Its general applicability was recently confirmed by a case study with pharmaceuticals. , The first scenario represents the situation of dry weather in summer (dry summer scenario), and the second one describes humid periods throughout the whole year (average flow scenario), where the flow rate is affected by interflow and surface runoff due to precipitation (see Table S9 for more details).…”
Section: Methodsmentioning
confidence: 99%
“…The GREAT-ER ( Geography-Referenced Regional Exposure Assessment Tool for European Rivers ) model is well established for simulating chemical exposure in whole river catchments. It has been successfully applied to predict environmental concentrations of different chemicals like detergents, pharmaceuticals, and even dissolved zinc in various catchments. Recently, it has been applied for risk assessment of selected pharmaceuticals in the Dutch–German transboundary catchment of the Vecht River .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complexity, there is no standard for modeling CECs in river systems (Keller, 2015). Various process-based and empirical water quality models such as EPA SWMM (Park et al, 2007;Jackson et al, 2011;Dittmer et al, 2020), SWAT (Wang et al, 2019), QUAL2K (Zhi et al, 2022), GREAT-ER, (Koormann et al, 2006;Sumpter et al, 2006;Lämmchen et al, 2021a;Lämmchen et al, 2021b), and WASP (Agustin et al, 2023), have been modified or developed to simulate the fate and transport of CECs (Sharma and Kansal, 2013). Others, more recently, have applied various machine learning approaches to simulate concentrations and loads of CECs in rivers (Yun et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…At this point, substance-routing models can be employed for river networks to understand the behavior of waterborne substances and track their spatiotemporal dynamics, especially when MEC data is scarce [27]. The predicted environmental concentrations (PEC) derived from modeling approaches can serve to fill the spatiotemporal gaps of monitoring programs and support to conduct ERA by screening of exposure risks with the comparison of PEC with the ecotoxicological thresholds PNEC|EQS [28][29][30].…”
Section: Introductionmentioning
confidence: 99%